Risk factors in developing amyloid related imaging abnormalities (ARIA) and clinical implications - Doran, Sarah J.; Sawyer, Russell P. (Frontiers in Neuroscience, 2024)
Alzheimer’s disease (AD) affects over 6 million people over the age of 65. The advent of new anti-amyloid monoclonal antibodies as treatment for early Alzheimer’s disease these immunotherapeutics may slow disease progression but also pose significant risks. Amyloid related imaging abnormalities (ARIA) identified on MRI following administration of these new monoclonal antibodies can cause both brain edema (ARIA-E) and hemorrhage (ARIA-H). While most ARIA is asymptomatic, some patients can develop headache, confusion, nausea, dizziness, seizures and in rare cases death. By analyzing lecanemab, aducanumab, gantenerumab, donanemab, and bapineuzumab clinical trials; risk factors for developing ARIA can be identified to mitigate some of the ARIA risk. Risk factors for developing ARIA-E are a positive Apoε4 carrier status and prior multiple cerebral microhemorrhages. Risk factors for ARIA-H are age, antithrombotic use, and history of prior strokes. With lecanemab, ARIA-E and ARIA-H were seen at lower rates 12 and 17%, respectively, compared to aducanumab (ARIA-E 35% and ARIA-H 19%) in treated patients. ARIA risk factors have impacted inclusion and exclusion criteria, determining who can receive lecanemab. In some clinics, almost 90% of Alzheimer’s patients are excluded from receiving these new anti-amyloid therapeutics. This review aims to discuss risk factors of ARIA and highlight important areas for further research. With more anti-amyloid monoclonal antibodies approved by the Food and Drug Administration, considering patient risk factors for developing ARIA is important to identify to minimize patient’s risk while receiving these new therapies.